The grit factor : courage, resilience, and leadership in the most male-dominated organization in the world - Polson, Shannon Huffman (Boston, MA : Harvard Business Review Press, 2020)
"Push through the pushback. At age nineteen, Shannon Huffman Polson became the youngest woman ever to climb Mt. McKinley. A native of Alaska, she went on to reach the summits of Mt. Rainier and Mt. Kilimanjaro and spent more than a decade traveling the world. Yet it wasn't until she joined the military, as one of the Army's first female attack helicopter pilots, and went on to lead platoons on deployment to Bosnia-Herzegovina, that she learned the secrets of leadership that changed her forever. Where did these insights come from? From her own crucibles of experience--and from other women. Polson made it her mission to become acquainted with an elite pack of tough, impressive female iconoclasts who shared their candid stories of combat and career. This decorated cast of characters includes Heather Penney, one of the first female F-16 pilots who was put on a "suicide mission" for 9/11; General Ann Dunwoody, first female four-star general in the Army; Marine Commander Amy McGrath, first woman to fly the F/A-18 in combat and a 2018 Congressional candidate--and dozens of other unstoppable women who got there first, including Polson herself. These women learned to lead at the highest levels in the most complicated, challenging, and male-dominated organization in the world. Now, in the post-#MeToo era, when all women can break through the barriers to lead, and when all of us are looking for inspiration and guidance to change institutional progress, Polson brings these voices together, sharing her own life lessons and theirs with storytelling flair, keen insight, and incisive analysis of current, relevant research. With relatable takeaways like "your story is your strategy" and "push through the pushback," The Grit Factor is both inspiring and pragmatic, a book that will motivate current and aspiring leaders everywhere--whether male or female"--
Introduction: Plotting a course for grit -- Section 1. Commit: Know your story -- Uncover your purpose -- Section 2. Learn: Draw your circle -- Listen like a leader -- Build your resilience -- Section 3. Launch: Turn your nose to face the wind -- Have the audacity to be yourself -- Above all else, be adaptable..
Includes index.
Keywords: Resilience (Personality trait); Toughness (Personality trait); Command of troops; Leadership; Sex discrimination against women; United States -- Armed Forces -- Women